Birth Interval and Twins Birth on Maternal Mortality in Indonesia: Cross-Sectional Study - Diva, Putri Royan; Fauzi, Lukman (Universitas Negeri Semarang (UNNES) in cooperation with the Association of Indonesian Public Health Experts (Ikatan Ahli Kesehatan Masyarakat Indonesia (IAKMI)), 2025)
Maternal mortality is a global-scaled health problem to indicate how good a health system is in a region. Indonesia reached 305 per 100.000 live birth as per 2017. That rate is still far from SDGs 2030 which suggests that every country has accomplished 70 per 100.000 livebirth. There are factor risks that caused maternal mortality. Those factors can be divided into individual character-related factors, socioeconomy-related factors, and healthcare-related factors. This study is an analytical study using cross-sectional design data from the DHS program 2017. Data were analyzed using bivariate analysis and multivariate analysis to fiigure out which variables that associate with maternal mortality. Preceding birth interval, succeeding birth interval, and twin birth status are the three main factor risks that associate with maternal mortality. It is recommended that Indonesian family needs to participate in family planning, including birth control in order to control the factor risks of maternal mortality.